Nde1 and Ndel1: Outstanding Mysteries in Dynein-Mediated Transport - Garrott, Sharon R.; Gillies, John P.; DeSantis, Morgan E. (Frontiers in Cell and Developmental Biology, 2022)
Cytoplasmic dynein-1 (dynein) is the primary microtubule minus-end directed molecular motor in most eukaryotes. As such, dynein has a broad array of functions that range from driving retrograde-directed cargo trafficking to forming and focusing the mitotic spindle. Dynein does not function in isolation. Instead, a network of regulatory proteins mediate dynein’s interaction with cargo and modulate dynein’s ability to engage with and move on the microtubule track. A flurry of research over the past decade has revealed the function and mechanism of many of dynein’s regulators, including Lis1, dynactin, and a family of proteins called activating adaptors. However, the mechanistic details of two of dynein’s important binding partners, the homologs Nde1 and Ndel1 have remained elusive. While genetic studies have firmly established Nde1/Ndel1 as players in the dynein transport pathway, the nature of how they regulate dynein activity is unknown. In this review, we will compare Ndel1 and Nde1 with a focus on discerning if the proteins are functionally redundant, outline the data that places Nde1/Ndel1 in the dynein transport pathway, and explore the literature supporting and opposing the predominant hypothesis about Nde1/Ndel1’s molecular effect on dynein activity.